2019
DOI: 10.1186/s12910-019-0414-6
|View full text |Cite
|
Sign up to set email alerts
|

Broad consent for biobanks is best – provided it is also deep

Abstract: Background As biobank research has become increasingly widespread within biomedical research, study-specific consent to each study, a model derived from research involving traditional interventions on human subjects, has for the sake of feasibility gradually given way to alternative consent models which do not require consent for every new study. Besides broad consent these models include tiered, dynamic, and meta-consent. However, critics have pointed out that it is normally not known at the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
73
0
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 25 publications
0
73
0
7
Order By: Relevance
“…These include, among others, specific consent (specific for a single research project), dynamic consent (using technology to allow participants to choose between broad consent or to approve a single study at a time), and tiered consent (where the participant allows some uses of the samples only and renewal of consent is needed for other studies [ 10 , 47 , 49 ]. A broad consent form that contains adequate details is regarded as a suitable model of consent for use in biobanks [ 50 ]. Broad consent should detail the nature of the biobank and types of samples and data to be collected [ 32 , 51 – 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These include, among others, specific consent (specific for a single research project), dynamic consent (using technology to allow participants to choose between broad consent or to approve a single study at a time), and tiered consent (where the participant allows some uses of the samples only and renewal of consent is needed for other studies [ 10 , 47 , 49 ]. A broad consent form that contains adequate details is regarded as a suitable model of consent for use in biobanks [ 50 ]. Broad consent should detail the nature of the biobank and types of samples and data to be collected [ 32 , 51 – 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…As noted in the literature, this can be challenging if collected samples may be used for future and as yet unspecified research. This process may be even more challenging if future research use involves the generation and/or sharing of genomic data 14 , 28 .…”
Section: Discussionmentioning
confidence: 99%
“…A broad consent mechanism covering these aspects is considered adequate to meet the informational needs of a prospective donor/participant, and is recognized to be acceptable for use by biobanks in the guidelines that we analyzed. This should be complemented by a robust ethics governance system, which usually includes a REC or institutional review board (IRB) where ethical requirements are concerned 7 , 10 , 12 , 13 , 28 . RECs/IRBs oversee biobanking activities to ensure that the process meet these specifications 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Proponents of such dynamic consent models have argued that broad consent can be viewed as ethically problematic (Budin-Ljøsne et al, 2017; Kanelloupoulou et al, 2011; Steinsbekk et al, 2013). An ethical analysis by Mikkelsen et al (2019) suggests that, when compared to other models of informed consent, a modified form of broad consent may be ideal. These modifications would include a continuous ethical review to evaluate whether proposed research falls within the scope of the broad consent.…”
Section: Discussionmentioning
confidence: 99%
“…These modifications would include a continuous ethical review to evaluate whether proposed research falls within the scope of the broad consent. Mikkelsen also recommends continuous provision of information to participants (Mikkelsen et al, 2019). Still, Majumder et al (2019) reported that while most researchers are in favor of expanding the role of participants beyond one-time, broad consent, they also raise concerns about the amount of this would require on the part of the researchers.…”
Section: Discussionmentioning
confidence: 99%